The Relationship between Employability Skills and Job Performance among University Graduates - Rodzalan, Shazaitul Azreen; Mohamad Jasman, Nurzunah (Research in Management of Technology and Business, 2022)
Employability skills refer to knowledge, skill, and attitude that function and enable that required at the workplace. The skills are important to ensure that graduates able to meet the demands set by the employer. However, there are still lacking of skills among graduates have been reported. In addition, the attitudes of graduates those are too choosy in selecting their job. The main research objective is to identify the level of employability skills, to examine the level of job performance and to investigate the relationship between employability skills and job performance among graduates. The method for this study is quantitative approach. The target population of this study were those graduates from eight faculties in public university in Malaysia. The questionnaire was distributed to 335 respondents. The findings shows that university graduates perceived to high level of employability skills and job performance. Findings also reveal that there is a positive relationship between employability skills and job performance, which most graduates used to develop in their self. This research would give benefits to the graduates to develop their skills in the future.